Electronic Patient-Reported Outcome Measures in Radiation Oncology: Initial Experience After Workflow Implementation - Hauth, Franziska; Bizu, Verena; App, Rehan; Lautenbacher, Heinrich; Tenev, Alina; Bitzer, Michael; Malek, Nisar Peter; Zips, Daniel; Gani, Cihan (JMIR Publications, 2019)
BackgroundMobile health (mHealth) technologies are increasingly used in various medical fields. However, the potential of mHealth to improve patient care in radiotherapy by acquiring electronic patient reported outcome measures (ePROMs) during treatment has been poorly studied so far. ObjectiveThe aim of this study was to develop and implement a novel Web app (PROMetheus) for patients undergoing radiotherapy. Herein, we have reported our experience with a focus on feasibility, patient acceptance, and a correlation of ePROMs with the clinical course of the patients. MethodsIn the period between January and June 2018, 21 patients used PROMetheus to score side effects, symptoms, and quality of life-related parameters during and after their treatment. Items of the Patient Reported Outcome version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) were chosen based on the primary site of disease, 27 items for head and neck tumors, 21 items for thoracic tumors, and 24 items for pelvic tumors. ResultsIn total, 17 out of the 21 patients (81%) regularly submitted ePROMs and more than 2500 data points were acquired. An average of 5.2, 3.5, and 3.3 min was required to complete the head and neck, thorax, and pelvis questionnaires, respectively. ePROMS were able to detect the occurrence of both expected and unexpected side effects during the treatment. ConclusionsThis study shows the successful implementation of an ePROM system and a high patient acceptance. ePROMs have a great potential to improve patient care in radiotherapy by providing a comprehensive documentation of symptoms and side effects, especially of ones that are otherwise underreported.